The Customer Buying Process Research Project - RAO, DI (2013)
It is estimated that many customers are not willing to pay for advices after RDR. Financial services firms are driven to either provide simplified and straightforward advices to save the cost for both consumers and the companies, or change to non-advised basis sales. This project researches the current buying process of Mutuals’ customers, in order to find out when and where customers need advices, and how the Mutuals help them along the purchase journey.